EVALUATION OF QUALITY OF TRAINING OF SPECIALISTS IN COLLEGES: THEORY, METHODOLOGY, PRACTICE (Innovative professional education, 2022)
Based on the analysis of the essential characteristics of pedagogical assessment, features of the competence approach in professional higher education, the theoretical and methodological aspects of assessing the quality of professional training in colleges are substantiated. The method of assessment of competencies (educational results) on the basis of didactic differentiation of professional actions is offered. The main stages of practical actions on the objective assessment of students' competence achievements are described.
Keywords: professional higher education; pedagogical assessment; quality of training; learning outcomes; colleges